The War on Terror: The Neo-American Manifest Destiny - Khelfa, Nouha (Faculty of Law Universitas Negeri Semarang, 2023)
Significant literature has concluded that Islamic-terrorist activity in the Middle East and in Europe had increased drastically since the beginning of the implementation of the Bush Doctrine in 2001 after 9/11, with the rise of ISIS. However, little is known about the causal mechanism that links between the Post-9/11 U.S. foreign policy and the rise of new terrorist organizations, particularly the Islamic State in Iraq. Hence, the focus of this study is to process trace such mechanism. It will also explain why the War on Terror has produced totally opposite results from those it was originally intended for. Finally, this study is a within-case analysis that might be a microscopic observation of the imperial American behavior in the Middle East. This study relies on explaining outcome process-tracing methodology, and employing oral and historical accounts, archives and statistical data. I argue that the War on Terror, precisely the period of the Bush’s presidency (2001-2009), to be the continuity of the historical imperial behavior that inspires the U.S. foreign policy. I will only focus on two main policies: the Invasion of Afghanistan in 2001 and the Invasion of Iraq in 2003 because invasion is the most concrete manifestation of imperialism. The result shows that the invasion of Iraq led to sectarianism that IS feeds on, and that the invasion of Afghanistan led to the geographical expansion of Jihadists. Together they fused to cause the mutation of Al-Qaeda into a more complex Islamic-inspired terrorist organization (IS).